RA03.03: THE IMPACT OF ENHANCED RECOVERY AFTER SURGERY (ERAS) ON PATIENTS UNDERGOING OESOPHAGECTOMY. (14th September 2018) - Dent, Barry; Sturrock, Jillian; Mckenna, Janine; Taylor, Claire; Jaretzke, Helen; Michael Griffin, S; Immanuel, Arul
Abstract: Background: Enhanced recovery after surgery (ERAS) is defined as a multimodal care pathway designed to achieve early recovery for patients undergoing surgery. For patients undergoing oesophagectomy such pathways are complex and must involve a wide multi-disciplinary team. The importance of peri-operative nutrition is especially relevant in this patient group. We describe our experience of the impact of an ERAS pathway in a high volume oesophago-gastric unit on both short and medium term patient outcomes. Methods: Consecutive patients undergoing open 2 phase subtotal oesophagectomy with two field lymphadenectomy in a 12 month period following the introduction of an ERAS pathway were included in the study. Outcomes were compared with consecutive patients undergoing the same procedure over a 12 month period prior to the introduction of the ERAS pathway. All patients were treated in a single UK unit. Adherence to the ERAS pathway was monitored by a dedicated ERAS coordinator. All data were collected prospectively. Statistical analysis was performed using the Mann-Whitney U test for continuous and Chi 2 for categorical data. Results: 189 patients were included (97 pre-ERAS and 92 ERAS). There were no demographic differences between the patient groups. The rate of severe post-operative complications (Accordion score 3 + ) was identical between groups (29%). Median length of hospital stay was significantly reduced with ERAS (10 days v 14 days pre-ERAS ( P  < 0.001)) as was the total readmission rate (21% v 39% P  = 0.006). Weight loss following surgery was significantly reduced with ERAS. At 2 weeks 1% of patients had lost over 10% of their pre-operative weight compared with 32% pre-ERAS ( P  < 0.001). A significant difference was maintained at 6 weeks (9% v 55%), 3 months (19% v 66%) and 6 months (35% v 71%). Conclusion: Our results demonstrate the positive impact of ERAS for patients undergoing oesophagectomy. Despite no reduction in post-operative complication rates, both hospital stay and readmission rates were reduced, suggesting a positive impact of ERAS on patients' response to complications. Far fewer patients were readmitted for nutritional reasons/failure to thrive following the introduction of ERAS. Implementing an ERAS pathway requires a dedicated multi-disciplinary team to provide the required peri-operative care both in the hospital and community. Disclosure: All authors have declared no conflicts of interest.